RETRACTED: Assessing the management student's entrepreneurial intentions: Role of entrepreneurship education and technology transfer - Wang, Zihan; Ortiz, Geovanny Genaro Reivan (Frontiers in Psychology, 2022)
Entrepreneurship educators who focus on sustainable development teach individuals how to maximize available resources while ensuring that future generations have access to those resources. This paper examines the impact of students' entrepreneurship education in China on their entrepreneurial intentions. Perceived entrepreneurial capacity, education in entrepreneurship, and attitudes toward entrepreneurship are all factors in the model developed to predict entrepreneurial intention. Structured equation modelling (SEM) is being used to test 98 management students from various universities in China. The study's findings show that entrepreneurship education, entrepreneurial attitude, and entrepreneurial intention are all found to be statistically related amongst management students. Moreover, technology transfer correlates statistically with students’ entrepreneurial intentions. Thus, universities are being encouraged to offer entrepreneurial training modules to increase their students' entrepreneurial intent.